Variação temporal da riqueza de táxons, abundância e biomassa de artrópodes em ambiente de restinga do Rio Grande do Norte, Brasil - Marques, Márdyla de Sousa (2013)
Arthropods are abundant organisms possess great wealth and diversity representing about 82% of all known animal species. Contribute as a source of biomass and their abundance is an indicator of ecological change. The aim of this study was to evaluate the biomass and abundance found in the salt marsh environment throughout the year and relate them to the climatic factors (temperature, precipitation and relative humidity) that can influence the abundance and biomass of arthropods. The study was conducted at the Centro de Lançamento de Foguetes Barreira do Inferno, city of Parnamirim, Rio Grande do Norte, in the period February 2011 to January 2012, using pitfall traps, stationary window and beating tray. Among the 26 orders found, the most abundant were: Hymenoptera, Orthoptera, Araneae. Taxa Hymenoptera, Blattodea and Orthoptera showed higher biomass volume. Climatic factors did not influence the fall of Arthropods in the traps, however, the lowest abundance during the rainy season the action of raindrops, reduced the activity of these arthropods on vegetation, reducing its capture in traps (pitfall traps and stationary window ) and method of collection(entomological umbrella)